Routine screening of harmful microorganisms in beach sands: implications to public health - Sabino, Raquel (2013)
Beaches worldwide provide recreational opportunities to hundreds of millions of people and serve as important components of coastal economies. Beach water is often monitored for microbiological quality to detect the presence of indicators of human sewage contamination so as to prevent public health outbreaks associated with water contact. However, growing evidence suggests that beach sand can harbor microbes harmful to human health, often in concentrations greater than the beach water. Currently, there are no standards for monitoring, sampling, analyzing, or managing beach sand quality. In addition to indicator microbes, growing evidence has identified pathogenic bacteria, viruses, and fungi in a variety of beach sands worldwide. The public health threat associated with these populations through direct and indirect contact is unknown because so little research has been conducted relating to health outcomes associated with sand quality. In this manuscript, we present the consensus findings of a workshop of experts convened in Lisbon, Portugal to discuss the current state of knowledge on beach sand microbiological quality and to develop suggestions for standardizing the evaluation of sand at coastal beaches. The expert group at the "Microareias 2012" workshop recommends that 1) beach sand should be screened for a variety of pathogens harmful to human health, and sand monitoring should then be initiated alongside regular water monitoring; 2) sampling and analysis protocols should be standardized to allow proper comparisons among beach locations; and 3) further studies are needed to estimate human health risk with exposure to contaminated beach sand. Much of the manuscript is focused on research specific to Portugal, but similar results have been found elsewhere, and the findings have worldwide implications.